Early Diagnosis of Abnormal Left Ventricular Systolic Functions of Rare Pathogenic Titin Mutation Gene Carriers in FHCM by Three-Dimensional Speckle Tracking Echocardiography Combined with Gene Detection - Xiang-hong Luo; Rui Zhu; Qian Chen; Pei-hong Shi; Li-sha Na (International Journal of Clinical Practice)
Objective. This study aimed to explore the early diagnosis of abnormal left ventricular systolic function of rare pathogenic titin (TTN) mutation gene carriers in familial hypertrophic cardiomyopathy (FHCM) by three-dimensional speckle tracking echocardiography (3D-STE) combined with gene detection. Methods. Eighteen members of a Hui nationality family in Ningxia province of China were enrolled in this study in July 2019. The proband was tested with high-throughput sequencing of gene detection technology to detect the whole exome, and the mutation locus of pathogenic TTN gene was analyzed. According to the result, 16 subjects were divided into two groups: carrier group (n = 4) and noncarrier group (n = 12). Related indicators from 2DE were obtained, and myocardial strain indicators from 3D-STE were analyzed by postprocessing software of Tomtec. Strain indicators included global longitudinal strain (GLS), global circumference strain (GCS), global radial strain (GRS), regional longitudinal strain (RLS), regional circumference strain (RCS), and regional radial strain (RRS). All those indicators were compared between the two groups, and a receiver operating characteristic (ROC) curve was used for further analysis. Results. There were 4 subjects diagnosed as asymptomatic TTN gene carriers with the mutation locus of Val135643Ile. Compared with the noncarrier group, GLS and partial RLS were significantly reduced in the carrier group. The ROC curve shows that GLS has the largest AUC, and its sensitivity was better than LVPWD and specificity was better than IVSD and LVMI obtained from 2DE in the carrier group. Conclusions. There were 4 subjects diagnosed as asymptomatic TTN gene carriers with the mutation locus of Val135643Ile, and their GLS and partial RLS were significantly reduced; GLS had the better sensitivity and specificity than LVPWD, IVSD, and LVMI.